The effect of tax planning, deferred tax expense, and earnings management on tax avoidance with corporate governance as a moderating variable - Rani Nur Az-zahra Osman; Wiralestari Wiralestari; Ilham Wahyudi; Enggar Diah Puspa Arum (Privietlab, 2026)
This study examines the effects of tax planning, deferred tax expenses, and earnings management on tax avoidance, with corporate governance as a moderating variable. The research sample comprises 52 manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 period, yielding 260 firm-year observation. Data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS) through SmartPLS 4. The findings reveal that tax planning, deferred tax expenses, and earnings management each have a significant positive effect on tax avoidance. Corporate governance effectively moderates (weakens) the relationship between tax planning and tax avoidance and between earnings management and tax avoidance. However, corporate governance does not significantly moderate the effect of deferred tax expenses on tax avoidance. These findings offer theoretical contributions to agency and tax compliance theories in the Indonesian context and provide practical implications for tax authorities, regulators, and corporate management in designing more effective oversight mechanisms to mitigate aggressive tax avoidance practices.